Evaluation of Sodium Carboxymethyl Starch obtained from Ipomoea Batatas - Mohammed Achor, James Yinka Oyeniyi, mahmud sani gwarzo, Aminu Zayyanu (Journal of Applied Pharmaceutical Science, 2015)
The study sought to evaluate the functional properties of sodium carboxymethyl starch obtained from Ipomoea batatas, in order to facilitate their exploitation as substitute excipients for the local pharmaceutical manufacturing industry. The sodium carboxymethyl starch was produced by reacting native starch with sodium hydroxide and sodium monochloroacetate in various proportions and reaction time at constant temperature. Subsequently, the starches were obtained by wet separation techniques. Physicochemical properties and proximate analysis were carried out in order to determine their suitability for pharmaceutical use. Differences in the physicochemical properties, proximate composition, and functional properties of sodium carboxymethyl starches and native Ipomoea batatas starch were significant. Optimum degree of substitution and reaction efficiency of 0.52 and 1.92% were achieved when sodium hydroxide and sodium monochloroacetate in a ratio 1.5 and 2.0 Mole per anhydrous glucose unite respectively in 6 hrs was used. Generally, the carboxymethyl starches had higher bulk density, tapped density, true density, hydration and swelling capacity as compared to the native starch.
Keywords: Ipomoea batatas, sodium carboxymethyl starch, sodium monochloroacetate.